Acute Lung Injury/Acute Respiratory Distress Syndrome: a Need for Education - Cedeño, Arturo; Galera, Angel; Torres, Alfonso; Rodríguez-Cintrón, William (Puerto Rico Health Sciences Journal, 2012)
see manuscript